Haemoglobinopathies encountered at Khoula Hospital, Oman A retrospective study - Gihan Adly; A Rajappa (Sultan Qaboos University Medical Journal, 2008)
Objective: The objective of this study was to find out the frequency of abnormal haemoglobins (Hb) in patients referred to Khoula Hospital, Oman and compare the data from other studies by assessing a large number of patients. Methods: The results of 27,403 patients, either admitted to Khoula Hospital or referred to it from different health centres during the 4 years of the study from January 2001 till December 2004, were analysed for haemoglobinopathies. The laboratory methods used for detection of abnormal haemoglobins were sickle cell solubility test and haemoglobin electrophoresis. Results: The frequency of sickle cell trait was 7.5%, sickle cell disease 0.46% and other Hb variants were 0.102%. The results correlate well with that of the National Genetic Blood Disorder Survey carried out by the research and studies department, Ministry of Health, Sultanate of Oman, during a 4 year period from January 2001 till December 2004. Conclusion: This retrospective study demonstrates the high prevalence of haemoglobinopathies among the studied group of patients. More attention to the importance of health education and genetic counselling is required for the prevention of this public health problem in the country.